(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Pigeon pea is an important grain legume in the tropics and subtropics and it is a valuable source of low-cost plant protein for humans and animals, but it remains an underutilized legume. Effects of feeding graded levels of raw pigeon pea seed inclusion diets on testicular function in Wistar rats was investigated. Thirty male Wistar rats weighing between 120 and 160 g were assigned into six groups (A-F) of 5 rats each. Group A rats served as the control and were fed with standard rat feed, Group B was fed with 10% pigeon pea inclusion diet, group C: 20% pigeon pea inclusion diet, Group D: 30% pigeon pea inclusion diet, Group E: 40% pigeon pea inclusion diet and Group F: 100% pigeon pea diet. Each rat received 30 g of feeds per day for 21 days with drinking water ad libitum. All analyses were carried out using standard methods. The motility scores were between 34.00±2.45 and 87.00±3.00 with the control group A having the significantly highest score (P<0.05) compared to the other groups. Group B rats had a significantly higher (P<0.05) values of (76.00±6.96) than groups C, D, E, and F while groups D, E and F were lower than normal range. This same trend was observed for the sperm viability and count across the groups. No lesion was observed in the testicular histology of rats in groups A, B, and D. The testis of rats in group C showed marked expansion of the interstitium by oedema, while the testis of group E rats showed immature germ cells in the seminiferous tubular lumen and the testis of group F rats revealed slightly reduced germinal depth. It was concluded in this study that feeding of pigeon pea seed diet to rats beyond 20% inclusion level is spermatotoxic having severe adverse effects on the sperm motility, viability and count and caused some testicular lesions. However, unprocessed pigeon pea must be incorporated with caution into animal feeds, especially the male animals used for breeding.